Reconstruction of the charged surface of liquid hydrogen - Kolmakov, G. V.; Levchenko, A. A.; Mezhov-Deglin, L. P.; Trusov, A. B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The evolution of shape of the surface of equipotentially charged liquid hydrogen film condensed on the lower or upper plate of a horizontally placed diode in external electric fields has been studied experimentally under the condition of total compensation of the applied field by the surface charge. Reconstruction phenomenon - the formation of a solitary wave (soliton)- has been observed in an electric field higher than some critical value for the film that covers the lower plate.